2011
DOI: 10.1051/0004-6361/201117103
|View full text |Cite
|
Sign up to set email alerts
|

Initiating molecular growth in the interstellar medium via dimeric complexes of observed ions and molecules

Abstract: A feasible initiation step for particle growth in the interstellar medium (ISM) is simulated by means of ab initio quantum chemistry methods. The systems studied are dimer ions formed by pairing nitrogen containing small molecules known to exist in the ISM with ions of unsaturated hydrocarbons or vice versa. Complexation energies, structures of ensuing complexes and electronic excitation spectra of the encounter complexes are estimated using various quantum chemistry methods. Møller-Plesset perturbation theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…In 1998, Mayer et al 22 reported the thermodynamic properties of the singlet C 2 H 2 N + isomers, and found the same ordering of the three lowest energy structures. They used Gaussian 2 (G2) theory as well as methods that include extrapolation to the one-particle basis set limit and found relative energies similar to those reported by Harland et al 23 In 1999, Lau et al 24 used G2 theory to examine the stability of C 2 H 2 N + isomers, including the lowest triplet structure (Figure 4, C s , 3 A"), and found the same order of stability for the singlet isomers, though the relative energies of the singlet isomers were somewhat different compared to the findings of Mayer et al, 22 with the lowest triplet isomer being slightly higher in energy than isocyanomethylene cation. In 2003, Di Stefano et al 25 examined the production of cations containing C-N bonds both experimentally and theoretically, including C 2 H 2 N + isomers.…”
Section: Introductionmentioning
confidence: 60%
“…In 1998, Mayer et al 22 reported the thermodynamic properties of the singlet C 2 H 2 N + isomers, and found the same ordering of the three lowest energy structures. They used Gaussian 2 (G2) theory as well as methods that include extrapolation to the one-particle basis set limit and found relative energies similar to those reported by Harland et al 23 In 1999, Lau et al 24 used G2 theory to examine the stability of C 2 H 2 N + isomers, including the lowest triplet structure (Figure 4, C s , 3 A"), and found the same order of stability for the singlet isomers, though the relative energies of the singlet isomers were somewhat different compared to the findings of Mayer et al, 22 with the lowest triplet isomer being slightly higher in energy than isocyanomethylene cation. In 2003, Di Stefano et al 25 examined the production of cations containing C-N bonds both experimentally and theoretically, including C 2 H 2 N + isomers.…”
Section: Introductionmentioning
confidence: 60%
“…The smaller molecules are pervasive and their interactions may help to understand how larger molecules or grains are formed in ISM [11]. Among important small species found in ISM are isothiocyanic acid HNCS (Sgr B2, 1979 [12]) and sulfur dioxide (Orion A, 1975 [13]).…”
Section: Introductionmentioning
confidence: 99%
“…Optimized structure of the next 6 lowest energy isomers of C 6 H 5 O + , at the CCSD(T)/cc-pVTZ level of theory. In ascending energy order, these isomers are 2methylene furanium ion or furfuryl cation (2), 3-methyl-furanium (3), hydroxycyclopentadiene (4), cyclopentenone ion (5), methyl-cyclopropyl ketone ion (6), and meta-cyclopentenone ion (7). Bond lengths are in Angstroms and bond angles are in degrees.…”
Section: Discussionmentioning
confidence: 99%
“…The vibrational frequencies of the C s symmetry non-planar (two hydrogen atoms out-of-plane) isomers (5,6,7) are presented in Table 6. These vibrational frequencies should be useful for identification of the corresponding isomers in future laboratory experiments and in the interstellar medium.…”
Section: Iiie Vibrational Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation